PXR-dependant dysregulation of glucose metabolism induced by chronic exposure to NOAEL-level pesticide cocktail in mice - Yannick Dauwe; Lucile Marie; Marina Grimaldi; Patrick Balaguer; Yannick Lippi; Veronique Gayrard; Laila Mselli-Lakhal (Environment International)
Pesticides are essential in modern agriculture but raise concerns about long-term metabolic effects, particularly through nuclear receptor activation. This study examines the impact of chronic exposure to a cocktail of five pesticides (dieldrin, propiconazole, boscalid, bupirimate, and pendimethalin) with or without tributyltin (TBT) on glucose and lipid metabolism in mice, focusing on the role of the constitutive androstane receptor (CAR) and pregnane X receptor (PXR). TBT was included for its strong affinity for RXR, a key heterodimerization partner of CAR and PXR, to assess whether RXR activation modulates or amplifies the metabolic effects of pesticide exposure. Results showed that pesticide exposure at NOAEL levels altered CAR and PXR dependent metabolic pathways. CAR knockout mice exhibited reduced free fatty acids and fasting glycemia, while PXR activation led to lower peak glycemia in oral glucose tolerance tests. Transcriptomic analysis identified disrupted pathways linked to glucose uptake and insulin sensitivity. These findings suggest that low-dose pesticide exposure can subtly affect metabolism via nuclear receptor interactions. The inclusion of TBT emphases RXR’s role in metabolic regulation. Overall, the study underscores the need to consider cocktail effects in risk assessment.